IDENTIFICATION OF THE RESPONSE PATTERNS PCI GIRDER BRIDGE STRUCTURE BASED ON LOCATION OF TRANSVERSE DIRECTIONS DAMAGE USING MIDAS CIVIL 2019 FINITE ELEMENT ANALYSIS - ZAINUDDIN FAKHRI, ZAKKI
Based on the high and low regions, the geographical condition of Indonesia is divided into three regions, namely coastal areas, lowlands and highlands. This proves that Indonesia really needs infrastructure that can connect all region in order to facilitate community mobility activities and improve the economic sector in each region. One of the infrastructure needed to connect access between regions in Indonesia is a bridge. However deterioration or damage to the bridge will certainly occur over time. Damage to the bridge is caused by various factors, including weather, enviroment, the burden borne and the age of the bridge. Efforts to maintain a bridge structure from deteriorating conditions can be done by conducting periodic inspections, which one is by installing sensors on the bridge. The output of the sensors requires a data bank that can be used as a reference in determining the condition of the bridge structure. This research was conducted with the aim of providing a data bank for use in testing bridge structure at field. To develop this research, it is necessary to do finite element analysis (FEA) with Midas Civil 2019, so that research can be carried out on examining the condition of the structure using dynamic response that occurs in modeling the bridge structure. The type of bridge to be examined in this study is the type of PCI Girder bridge with a span of 40.8m and CTC 1.85 m. The structural behavior values reviewed on the bridge modeling in the FEA are the period of the structure, frequency and deformation due to variations in the level of damage, location of damage and vehicle loads.